Temperate-Tropical Variation in Breeding Synchrony and Extra-Pair Paternity Among New World Tachycineta Swallows - Valentina Ferretti (Nature Portfolio, 2019)
Abstract Extra-pair paternity rates vary markedly across avian taxa, but patterns of variation in this trait have been obscured by a paucity of data on closely related species, especially those spanning broad environmental gradients. Here we compare variation in extra-pair paternity rates among five species in the widespread swallow genus Tachycineta. Rates of extra-pair paternity vary widely in this group, ranging from 13 to 87% of nests having extra-pair young. The inter-specific variation in extra-pair paternity within this small group of closely related swallows has a range equivalent to that found among all Hirundinidae and is close to the range of variation across all birds. Despite theory that predicts extra-pair paternity rates to be explained by latitudinal variation in breeding synchrony our results show that extra-pair paternity rates in this genus do not closely track a latitudinal gradient, as predicted by studies of other life-history traits, and are not explained by differences in breeding synchrony as previously suggested. The genetic mating systems of birds, described by the rates of extra-pair paternity, are connected to all other life-history traits through a complex network of trade-offs with organismal (phylogenetic) and ecological (environmental) factors. Disentangling each of these interactions to understand latitudinal patterns in any given life-history trait remains a daunting task.